AB0514 Bisphosphonates versus infliximab in ankylosing spondylitis treatment. (23rd January 2014) - Viapiana, O.; Fracassi, E.; Caimmi, C.; Idolazzi, L.; Dartizio, C.; Zampieri, R.; Montanari, I.; Troplini, S.; Povino, M. R.; Orsolini, G.; Gatti, D.; Rossini, M.; et al.
Abstract : Background: Ankylosing spondylitis (AS) is a chronic, inflammatory rheumatic disease characterised by inflammatory back pain due to sacroiliitis and spondylitis. TNF-α blocking agents (infliximab, etanercept, adalimumab and golimumab) are effective in controlling inflammation and pain and improving functionality in AS but are much more expensive than conventional treatments and they are contraindicated in some conditions. Objectives: Recognition of the importance of subchondral bone marrow inflammation in AS, together with in vitro and animal model data indicating that bisphosphonates may possess anti-inflammatory properties, constitute a theoretical rationale for their evaluation in this disease. Methods: This was a 6-month open randomized study on active AS conducted in a single center. After a 4-week run-in period, sixty patients were consecutively randomized in a 1:1 ratio to receive either neridronate (100 mg in 250 mL over 2 hours) or infliximab (5 mg/kg in 250 ml of sodium clorure 9% solution over 2 hours). Results: A significant reduction in the mean BASDAI was observed over 6 month neridronate or infliximab administration. BASDAI decreased by 1, 54 (30, 7%) (p<0, 05 versus baseline) and 1, 43 (29, 5%) (p<0, 05 versus baseline) at 3 months and by 1, 72 (35, 6%) (p<0, 05 versus baseline) and 1, 62 (32, 0%) (p<0, 05 versus baseline) at the end of study respectively in the neridronate and in the infliximab group. In the neridronate group main BASFI decreased by 0, 64 (p=0, 052 versus baseline) and by 0, 49 (p=0, 054 versus baseline) at 3 and 6 months. In the infliximab group we observed a significant reduction at 3 months (-0, 88 p=0, 005 versus baseline) but not at 6 months (-0, 61 p=ns). The VAS for axial pain decreased by 1, 9 cm at 3 months (p=0, 001 versus baseline) and by 2, 2 cm by 6 months (p<0, 0001 versus baseline) in the neridronate group. In the infliximab group the VAS changes were 1, 6 at 3 month (p=0, 03 versus baseline) and 2.2 at 6 months (p=0, 007 versus baseline). Differences between treatment arms were not significant at 3 months and at the final assessment. BASMI was not significantly modified in both neridronate and infliximab groups. No significant BMD variations were observed at 6 months in the infliximab group. In patients treated with neridronate a significant increase was observed at the lumbar spine BMD (p<0, 05 versus baseline and versus infliximab) but not at the hip sites. Conclusions: In this study we have shown that high IV doses of the amino-bisphosphonate neridronate are effective in reducing symptoms of disease in AS patients. The size effect at 6 months is similar to that obtained with standard infliximab therapy with additional benefits on BMD changes. Further studies to confirm these results over considerably longer timeframe are warranted together with the possibility to explore the long-term efficacy of a combination of anti-TNF and bisphosphonates. Disclosure of Interest: None Declared